Effects of birth spacing on adverse childhood health outcomes: evidence from 34 countries in sub-Saharan Africa. (17th October 2020) - Yaya, Sanni; Uthman, Olalekan A.; Ekholuenetale, Michael; Bishwajit, Ghose; Adjiwanou, Vissého
Abstract: Background: Interpregnancy intervals (IPI) are independently associated with maternal, perinatal, infant and child outcomes. Birth spacing is a recommended tool to reduce adverse health outcomes especially among children. This study aims to determine the prevalence of adverse child health outcomes in sub-Saharan Africa (SSA) countries and to examine the association between the length of preceding birth interval child health outcomes. Methods: Secondary data from Demographic and Health Survey (DHS) in 34 SSA countries with 299 065 births was used in this study. The outcome variables were infant mortality, low birth weight, stunting, underweight, wasting, overweight and anemia. Percentage was used in univariate analysis. Cox proportional hazard regression was used to examine association between the adjusted model of preceding birth interval and infant mortality. Multinomial and binary logistic regression models were used to examine the association between under-five children adverse health outcomes and interpregnancy birth interval. Results: Infant mortality was lowest in Gambia (3.4%) and highest in Sierra Leone (9.3%). Comoros (16.8%) accounted for the highest percentage of low birth weight (<2.5 kg). Child stunting was as high as 54.6% in Burundi. IPIs of <24 months, 24–36 months, 37–59 months and ≤60 months accounted for 19.3, 37.8, 29.5 and 13.4% respectively. Median IPI was 34 months. Results from Cox proportional hazard regression showed that children with preceding birth interval <24 months had 57% higher risk of infant mortality, compared to children with IPI of 24–36 months (Hazard ratio (HR) = 1.57; 95%CI: 1.45, 1.69). However, there were 19% and 10% reduction in the risk of infant mortality at IPIs of 37–59 months and ≥60 months, compared to 24–36 months IPI (37–59 months: HR = 0.81; 95%CI: 0.75, 0.87; ≥60 months: HR = 0.90; 95%CI: 0.81, 0.99). Conclusion: The findings of this study suggest the need for urgent intervention to promote the recommended interpregnancy interval of 24–36 months to reduce adverse child health outcomes. These data also bring into limelight the importance of exclusive breastfeeding to enhance proper nutritional approach and to prolong lactational amenorrhea. Health care system stakeholders would find this study interesting as a base for policy formulation and implementation.